Electrochemical Characterization of Immobilized Glucose Oxidase on Matrix of Graphene-Ion Liquid Composite - Liu, Hao-yu; Liu, Yan; Zhang, Xian-yu; Xu, Ze-min; Liu, Biao (Asian Journal of Chemistry, 2012)
The graphene-ion liquid nanocomposite (IL-GNs), characterized by good conductivity, high stability and good biocompatibility, provides a suitable biosensing matrix. Enzymes can be firmly incorporated into the matrix without the aid of other cross-linking reagents. Based on this, the glucose oxidase (GOD) is entrapped in the composite of IL-GNs and the direct electron transfer reaction between glucose oxidase and electrode takes place. The electron transfer rate of glucose oxidase is greatly enhanced to 6.7 s-1 in the system. It demonstrates that the conformational change of glucose oxidase in the microenvironment enables the accessibility of active site for glucose oxidase to the electrode. In addition, a third-generation glucose biosensor has been developed. The amperometric response of this sensor to glucose is observed with a linear range between 0.2 mM to 5 mM and a detection limit of 30 μM. The facile procedure of immobsilizing glucose oxidase will promote the developments of electrochemical research for protein, biosensors and other bio-electrochemical devices.